Effect of Heat Treatment on Corrosion Resistance of Stainless Iron - Clarence Merritt (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
STAINLESS iron, as mild stainless steel is usually called, an alloy ranging from 11.50 to 15.00 per cent chromium with carbon under 0.12 per cent, has been considered to be not appreciably affected in respect to corrosion resistance by heat treatment. This metal, while one of the most widely used of the "straight" chromium stainless alloys, has failed in many applications because of insufficient information regarding heat treatment. These failures have been attributed to many possible causes from an inherent lack of resistance to corrosion and misapplication to mysterious electrolytic effects or comparatively minute non-metallic inclusions. Many uses for a steel with such excellent physical properties is are latent in this alloy have been lost on account of corrosion failures which could have been avoided by applying proper heat treatment. The alloy has not received the recognition or attention it should because of the fact that' the details of its metallurgical behavior were not thoroughly understood. Response to heat treatment of the steel is well known as regards tensile properties, 1,2 but its application has been for improvement in tensile characteristics or on account of machining considerations rather than for corrosion prevention. The potential user of this steel has not been clearly advised in papers, either technical or commercial, that have been written about it in the last 10 years or more, of particular features that are of prime importance in developing the excellent properties of this metal. The data to be presented in this paper are concerned mainly with the effect of heat treatment on the corrosion resistance, but a study has also been made of the concurrent microstructural changes and an explanation developed for the phenomena revealed, as well as a correlation to the other physical properties-hardness, tensile characteristics and impact strength. Stainless steel, largely used for cutlery purposes, an alloy of approximately 13.00 per cent Cr with 0.30 per cent C, must be hardened and the surface prepared by polishing or pickling for best resistance to staining and corrosion.3 Monypenny reports that a loss of hardness is